2010
DOI: 10.1136/jnnp.2008.170092
|View full text |Cite
|
Sign up to set email alerts
|

Psychological approaches to treatment of postconcussion syndrome: a systematic review

Abstract: Background and aim Postconcussion syndrome (PCS) is a term used to describe the complex, and controversial, constellation of physical, cognitive and emotional symptoms associated with mild brain injury. At the current time, there is a lack of clear, evidence-based treatment strategies. In this systematic review, the authors aimed to evaluate the potential efficacy of cognitive behavioural therapy (CBT) and other psychological treatments in postconcussion symptoms. Methods Four electronic databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 56 publications
3
109
0
4
Order By: Relevance
“…15 This review also discussed CBT, which is a form of psychological intervention that focuses on identifying and changing patterns of maladaptive thinking and behavior that can exacerbate, or in some cases even cause, affective symptoms often associated with persistent effects of direct brain injury, including depression and anxiety. Three RCTs and 7 other studies of CBT all found some benefit, although there were limitations in study design.…”
Section: Psychological Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This review also discussed CBT, which is a form of psychological intervention that focuses on identifying and changing patterns of maladaptive thinking and behavior that can exacerbate, or in some cases even cause, affective symptoms often associated with persistent effects of direct brain injury, including depression and anxiety. Three RCTs and 7 other studies of CBT all found some benefit, although there were limitations in study design.…”
Section: Psychological Interventionmentioning
confidence: 99%
“…9 The differential diagnosis of PCS includes depression, somatization, chronic fatigue, chronic pain, cervical injury, vestibular dysfunction, ocular dysfunction, or some combination of these conditions. 15 The challenge for clinicians is to determine whether prolonged symptoms after concussion reflect a prolonged version of the concussion pathophysiology versus a manifestation of a secondary process such as premorbid clinical depression, a cervical injury, or migraine headaches. 16,17 It is therefore essential that the clinician obtain a history of prior affective or medical problems, perform a careful physical examination, and consider the response to exertion (ie, whether exertion reliably exacerbates symptoms) 18 when developing the differential diagnosis of persistent post-concussion symptoms.…”
Section: Definition Of Post-concussion Syndromementioning
confidence: 99%
“…Yet, there is a growing body of literature supporting the use of cognitive-behavioral therapy (CBT) to reduce symptoms of anxiety and depression following TBI (Bryant, Moulds, Guthrie, & Nixon, 2003;Fann, Hart, & Schomer, 2009). Studies have found that individuals with a mild TBI who receive a brief cognitive-behavioral intervention reported shorter symptom duration and significantly fewer symptoms 6 months after injury than do groups receiving routine care (Al Sayegh, Sandford, & Carson, 2010).…”
mentioning
confidence: 98%
“…[50] BDT'nin baş ağrısı, uykusuzluk gibi fiziksel belirtilerle birlikte depresyon ve anksiyete gibi psikiyatrik belirtilere de iyi geldiği ancak bilişsel işlevlerde anlamlı düzel-me sağlamadığı bildirilmektedir. [22] NICE(National Institute for Health and Clinical Excellence) kılavuzunda PKS tedavisinde BDT egzersizle birlikte en etkin tedavi yaklaşımı olarak önerilmektedir. [22] Psikiyatride Güncel Yaklaşımlar -Current Approaches in Psychiatry…”
Section: Bilişsel Davranışçı Tedaviunclassified